Análisis de los riesgos operativos derivados del factor personas, que impiden el desarrollo e incremento de proyectos de las pymes en el sector de la seguridad privada en el Distrito Metropolitano de Quito, durante el año 2013 - Guarnizo Cedeño, Jean Pierre (2015)
The topic proposed has been developed to verify the operational risks of human resource that affect the interests of the companies studied, also with this research will be shown which were the risks that had a greater impact. This graduate work is composed of four chapters that be described below: The first chapter have all bibliographic information, theoretical and scientific about security firms and private security, besides concepts, definitions and important factors that are part of operational risk. The chapter 2 shows the methodology that will be used throughout the investigation in addition to important aspects, such as the sample of companies studied, the model of the questionnaire used for the survey and its features. The chapter 3 shows information about the procedures used by the companies investigated, we also discuss some important aspects about the management of human talent and its major conflicts. Finally we have chapter 4 where the data obtained in the investigation were tabulated, also for better compression the results were analyzed and graphed. With this information and the data obtained through the research techniques used, we developed management indicators to analyze some specific factors. Finally we established conclusions and recommendations will serve as an aid in the development of the activities undertaken by staff in these companies.